A Comparison of Nurses’ and Patients’ Recognition of High-touch Surfaces in a Hospital Room - Yeon-Jeong Heo; Jae Sim Jeong; Hye Ran Choi; Yeon Hee Kim (Nursing and Health Sciences Journal (NHSJ), 2023)
This study was conducted to identify and compare areas perceived to be high-touch surfaces in patient hospital rooms by ward nurses and inpatients to prioritize cleaning and disinfection of these areas and also to improve hospital environment management. The participants were 122 nurses who worked in general hospital wards and 56 patients hospitalized at a 299-bed general hospital in Seoul. We selected 38 items from the high-touch surfaces identified by patients in previous studies and guidelines and classified them into 4 categories. For each item, the contact frequency was investigated with a self-report questionnaire on a graphic rating scale that contained 11 points. Data were collected from April 1, 2020, to April 30, 2020. The average recognition score of the frequency of high-touch surfaces was significantly higher in nurses than in patients. (5.96 ± 1.47 vs. 2.35 ± 1.98, p<0.001). The top seven high-touch surfaces included intravenous poles, bedrails, bed height remote controls, bedside tables, restroom door handles, bedside personal locks, and restroom seats, and the ranking of these surfaces was different between nurses and patients. While nurses and patients showed a consensus when identifying major high-touch surfaces, there was a big difference in their perception of these areas’ touch frequency. This study will help to understand and establish categories and criteria for high-touch surfaces in the future.